A ausência/presença de artigo definido diante de antropônimos em três localidades de Minas Gerais: Campanha, Minas Novas e Paracatu - Eduardo Tadeu Roque Amaral (2003)
The present work describes the absence/presence of the definite article before proper nouns (anthroponymy) as a variable areal phenomenon in Minas Gerais. Many works which deal with the definition and characterization of the proper noun - especially the anthroponymy - and of the definite article are discussed. Some research on the absence/presence of the definite article before anthroponymies are also commented. The research is based upon some theoretical and methodological support of Dialectology and Variationist Sociolinguistics. The corpora are constituted by contemporary oral language records collected in the municipal districts of Campanha, Minas Novas and Paracatu, with informants from two different age groups and also two school levels. For the quantitative treatment of collected anthroponymies occurrences, the variable data analysis program Goldvarb 2001 is used. In the quantitative analysis of data, factors favouring or disfavouring the absence/presence of the definite article before anthroponymies are identified. The existence of regional variation of the studied phenomenon raised by Moisés (1995) and Mendes (2000) is confirmed. It is also proved the possibility of delimitation of linguistic areas considering syntactic phenomena, which has not been done in the tradition of dialectological studies. Based on this, it is also pointed out the possibility of the existence of linguistic areas in Minas Gerais that do not coincide with the ones proposed by Zágari (1998), based mainly on phonetic and lexical phenomena. Other structures involving the anthroponymy are also commented: when it is preceded by demonstratives, or it is in a genitive construction, it is followed by adjectival complements or it is a toponymy.